The Trypanosome Exocyst: A Conserved Structure Revealing a New Role in Endocytosis. - Cordula M Boehm; Samson Obado; Catarina Gadelha; Alexandra Kaupisch; Paul T Manna; Gwyn W Gould; Mary Munson; Brian T Chait; Michael P Rout; Mark C Field (PLoS Pathogens)
Membrane transport is an essential component of pathogenesis for most infectious organisms. In African trypanosomes, transport to and from the plasma membrane is closely coupled to immune evasion and antigenic variation. In mammals and fungi an octameric exocyst complex mediates late steps in exocytosis, but comparative genomics suggested that trypanosomes retain only six canonical subunits, implying mechanistic divergence. We directly determined the composition of the Trypanosoma brucei exocyst by affinity isolation and demonstrate that the parasite complex is nonameric, retaining all eight canonical subunits (albeit highly divergent at the sequence level) plus a novel essential subunit, Exo99. Exo99 and Sec15 knockdowns have remarkably similar phenotypes in terms of viability and impact on morphology and trafficking pathways. Significantly, both Sec15 and Exo99 have a clear function in endocytosis, and global proteomic analysis indicates an important role in maintaining the surface proteome. Taken together these data indicate additional exocyst functions in trypanosomes, which likely include endocytosis, recycling and control of surface composition. Knockdowns in HeLa cells suggest that the role in endocytosis is shared with metazoan cells. We conclude that, whilst the trypanosome exocyst has novel components, overall functionality appears conserved, and suggest that the unique subunit may provide therapeutic opportunities.